2000
DOI: 10.2223/jped.164
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of child and adolescent nutritional status

Abstract: Objective: To present a review on the methods of assessment of the nutritional status of children and adolescents, emphasizing anthropometry and the various methods of evaluation of body composition, and discussing their advantages, limitations and risks.Methods: Chapters of textbooks, theses, articles relevant to the theme, as well as personal files and previous publications of the authors were selected.Results: Anthropometry, which consists of the assessment of physical dimensions and global composition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
18

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
2
14
0
18
Order By: Relevance
“…According to the III State Health and Nutrition Survey [Pesquisa Estadual de Saúde e Nutrição (PESN III)] (22) , held in 2006 with children under 5 years old in the state of Pernambuco, the prevalence of stunting was 7.7%, well below the value found in this study. However, Sigulem et al (23) found a similar result to that here described, with 25% of patients presenting impaired linear growth. In a study involving 749 children and adolescents hospitalized in the pediatric surgery at Hospital São Paulo, there was a percentage of 19% for short stature or risk for short stature (24) .…”
Section: Discussionsupporting
confidence: 88%
“…According to the III State Health and Nutrition Survey [Pesquisa Estadual de Saúde e Nutrição (PESN III)] (22) , held in 2006 with children under 5 years old in the state of Pernambuco, the prevalence of stunting was 7.7%, well below the value found in this study. However, Sigulem et al (23) found a similar result to that here described, with 25% of patients presenting impaired linear growth. In a study involving 749 children and adolescents hospitalized in the pediatric surgery at Hospital São Paulo, there was a percentage of 19% for short stature or risk for short stature (24) .…”
Section: Discussionsupporting
confidence: 88%
“…In the study, the nutritional status of children and adolescents with P. vivax malaria were assessed using anthropometrics measures, of which values are related to genetic and environmental characteristics [17,20,21]. The nutritional indexes derived from anthropometric measures were classified according to the regional and national standards [18].…”
Section: Discussionmentioning
confidence: 99%
“…The relation height-for-age was chosen to assess the associations of the nutritional status with the history of the disease and with parasitemia at admission since it is a more reliable estimation of a long-term impact on nutrition. Other nutritional indexes based on patient weight, such as weight-for-age and body mass index-for-age may suffer considerable changes in the acute phase of several diseases [17,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Os dois primeiros anos de vida são caracterizados por uma fase de crescimento acelerado e por importantes aquisições no processo de desenvolvimento, representando, assim, um período de grande vulnerabilidade aos agravos sociais, econômicos e ambientais 2 . O retardo de crescimento linear ou déficit estatural é uma medida de desnutrição a longo prazo, a qual geralmente está associada a uma combinação de consumo alimentar inadequado e infecções de repetição que estão intimamente relacionados com o padrão de vida da população, incluindo o acesso a alimentação, moradia e assistência à saúde [3][4][5] . O déficit estatural aumenta o risco de doenças infecciosas e mortalidade precoce, bem como pode acarretar comprometimento do desenvolvimento psicomotor, atraso na capacidade intelectual, menor capacidade produtiva na idade adulta, além de ser considerado determinante do baixo peso ao nascer entre as futuras gestantes 5,6 .…”
Section: ▄ Introduçãounclassified